Pergeseran Penguatan Sumber Daya Manusia Di Sektor Yang Minimal Dampaknya Terhadap Pandemi Covid-19 - Saputro, Wahyu Adhi; Ningrum, Restie Novita (Universitas Veteran Bangun Nusantara, 2021)
The COVID-19 pandemic has had an impact on all countries, both in terms of the economy and in other aspects, including Indonesia. Many sectors are affected by this pandemic, but the agricultural sector is a sector that is able to survive (sector of the last resort). This study aims to determine the possibility of strengthening human resources in the agricultural sector by diverting workers affected by COVID-19 to the agricultural sector. The method used in this research is descriptive analytical method. The data used is secondary data which is annual data that comes from relevant sources from several relevant ministries. Data analysis used in this research is trend analysis and strategy analysis. Based on the results of the study, it can be seen that the trend of increasing the daily spike in Covid-19 cases in Indonesia in 2020 is positive. Based on the results of the study, it can be seen that the trend of increasing layoffs in 2014-2020 is positive. Based on the results of the study, it can be seen that the trend of the development of the younger generation in the agricultural sector until 2019 is negative. Based on the results of the study, it can be seen that the trend of increasing the daily spike in Covid-19 cases in Indonesia in 2020 is negative. The solution for improving human resources can be done by providing opportunities and opportunities for human resources who experience layoffs to work in the agricultural sector which requires a lot of manpower. Of course, you need to be equipped with several things because these workers do not have experience in agriculture.